Expectations and Experiences of Information Literacy Instruction - Pohjola-Ahlin, Saga (Nordic Journal of Information Literacy in Higher Education, 2016)
In May 2016, 48 third semester undergraduate students enrolled in the physiotherapy program at Karolinska Institutet in Sweden were given three sets of questionnaires; before the information literacy instruction (ILI) started, at the end of the first session, and a week after, at the end of the second and last session. The aim of this small-scale pilot study was to shed some light on students’ motivation to attend ILI, how they value the sessions afterwards and how they assess their learning outcome. Furthermore, it was an attempt to do a "students’ user experience study” in a pedagogical setting, with the intention to evaluate and improve teaching in ILI to meet student expectations. The average response rate for the three questionnaires was 92%. The results show that students’ expectations were similar to the actual content of ILI, and that the students were satisfied with their own learning outcome. Both motivation and the sense of relevance got higher scores after students attended ILI. Motivation rose from 7,4 to 8,12 out of 10. This is positive because a high level of motivation often improves the learning outcome (Schunk, 2012). When asked which areas most needed improvement in order to further enhance their learning outcome, the most common responses were “the pedagogy” and “my own achievement”. It would be interesting to start collaborating with a group of students in order to explore new methods and learning activities.